Mikołaj Kornicz — polski husyta oczami historyka ustroju i prawa - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Mikołaj Kornicz Siestrzeniec was one of the best known Polish participants in the Hussite movement. A lot of information about him, mainly in the form of entries in court registers, has survived, which makes it possible to say that Mikołaj Kornicz was a typical child of his era. Drawing on the example of such a figure, a historian of the state and law can study various actions with regard to their lawfulness (or unlawfulness) at the time.
Keywords: Kornicz Mikołaj (zm. ok. 1445); historia państwa i prawa - XV w.; księgi miejskie i sądowe